Sociolinguistic Variations and Identity Negotiation Among Urban Youth in Multilingual Communities - Wiwi Winarti (Journal of Mandalika Social Science, 2025)
Sociolinguistic variations in multilingual communities reflect the complexity of the relationship between language and identity, particularly among urban youth. This study uses a qualitative method based on literature studies to explore how youth in urban environments utilize language choices to negotiate their social, cultural, and personal identities. Analysis of relevant literature shows that youth use code shifts, language hybridity, and linguistic innovation as adaptive strategies to the social dynamics presented by urbanization and globalization. In a multilingual community, language choice serves not only as a means of communication, but also as a symbol of cultural affiliation, resistance to homogenization, and expression of social mobility. Youth actively build their identities through interactions in social spaces, both physical and digital, which often reflect the tension between local authenticity and global influence. This negotiation of linguistic identity in urban spaces emphasizes the importance of contextual understanding of the role of language in shaping dynamic social structures. This article contributes to sociolinguistic studies by underlining the relationship between linguistic variation and identity construction in multilingual urban environments, while highlighting the theoretical and practical implications for the management of linguistic diversity in the modern era.